الشيخُ عَابِدين الكُنتي ودورُه في مقاومةِ التوسُّع الفرَنسِي بالصَّحراءِ الكُبرى (1894-1927م - بوسعيد, أحمد (جامعة الوادي - University of Eloued, 2022)
من الأُسَر ذائعةِ الصيت التي امتدَّ نفوذها بين ضفتي الصحراء لقرون متوالية أسرةُ "آل كُنتة" العريقة، وذلك بفضلِ جهودها الدينية، الاجتماعية والعلمية البيِّنة. يُضاف إلى تلك المآثر دورٌ جهادي تصدَّى له بعضُ منتسِبي هذه الأسرة، أعقَبَ احتلالَ مدنٍ ومناطقَ هامَّة، مثل: تنبكتو، أغداس، عين صالح، توات وولاتة. ترنو هذه الدراسة إلى تبيان الدور الجهادي لأحد أولئك الكنتيين، وهو الشيخ عابدين بن امحمد الكنتي، الذي برز اسمُه إثر غزو الفرنسيين لمدينة تنبكتو سنة 1894م، واستمرَّ يقارعهم في مثلث التقاطع الجغرافي الحضاري بين أزواد، شنقيط، وجنوب الجزائر، ممَّا أدَّى إلى إعاقة حركة التوسع الفرنسي نحو أقاليم وحواضر الصحراء الكبرى. The ancient Kuntas family is among the well-known families that had a widespread influence in the great desert for many centuries. The high-class position that the family had was mainly due to its religious, social, and scientific efforts. In addition to this, some members of this family had noticeable roles in fighting the French colonisation, especially when the latter had invaded Timbuktu, Agadez, Ain Saleh, Touat, and Walatah. This study points out the revolutionary efforts of Sheikh Abidin Ben Amhamed Al Kunti in facing the French expansion, whom his name stood out after the French invasion to Timbuktu in 1894. Moreover, the expansion movement of the French towards the regions of the great desert was hampered by Sheikh Abidin’s revolution in the triangle geographical crossroad of Azawad, Chinguetti, and the south of Algeria.
مقال
Keywords: عابدين الكنتي؛ الصحراء الكبرى؛ التوسع الفرنسي؛ الطوارق؛ أزواد; Abidin Elkunti; great desert; French expansion; Touareg; Azawad